A novel method for using RNA‐seq data to identify imprinted genes in social Hymenoptera with multiply mated queens - Howe, J; Schiøtt, M; Li, Q; Wang, Z; Zhang, G; Boomsma, JJ (Wiley, 2020)
Genomic imprinting results in parent‐of‐origin dependent gene expression biased towards either the maternally‐ or paternally‐derived allele at the imprinted locus. The kinship theory of genomic imprinting argues that this unusual expression pattern is a manifestation of intra‐genomic conflict between the maternally‐ and paternally‐derived halves of the genome that arises because they are not equally related to the genomes of social partners. The theory thus predicts that imprinting may evolve wherever there are close interactions among asymmetrically related kin. The social Hymenoptera with permanent caste differentiation are suitable candidates for testing the kinship theory because haplodiploid sex determination creates strong relatedness asymmetries and nursing workers interact closely with kin. However, progress in the search for imprinted genes in the social Hymenoptera has been slow, in part because tests for imprinting rely on reciprocal crosses that are impossible in most species. Here, we develop a method to systematically search for imprinting in haplodiploid social insects without crosses, using instead samples of pooled individuals collected from natural colonies. We tested this protocol using data available for the leaf‐cutting ant Acromyrmex echinatior, providing the first genome‐wide search for imprinting in any ant. While we identified several genes as potentially imprinted, none of the four genes tested could be verified as imprinted using digital droplet PCR, highlighting the need for higher quality genomic assemblies that accurately map duplicated genes.